LITERASI BUDAYA BALI : KAJIAN FILSAFAT ILMU TENTANG KEADILAN DALAM SISTEM SUBAK - I Gusti Agung Alit Suryawati; I Gusti Ngurah Nitya Santhiarsa (Jurnal Nomosleca, 2020)
Subak is one of the local wisdoms in Bali where subak is a social organization that specifically regulates the irrigation system used in rice cultivation, where members of this subak are farmers who own land or smallholders in a particular agricultural area. The essence of Subak is the method of equitable distribution of water. The study method used is the study of the philosophy of ontology, epistemology and axiology. About justice in the subak system. Based on the results of the study it was concluded that in the existing subak system in Bali, the justice system that is used, in the water distribution system to every farmer uses a combination or combination of Commutative Justice and Distributive Justice where the water distribution must include all paddy fields of each member, meaning all members subak get their rights, then the distribution is based on weighting, where the amount of rights received by each farmer is based on the condition of the land owned but the obligations are adjusted to the rights that have been received.Keywords: subak, philosophical studies, justiceDOI: https://doi.org/10.26905/nomosleca.v6i1.3960